Implementation of Child Marriage Prevention Policy in Order to Realize a Child-Friendly District in Bangka Regency - Hudirman, Andi; Arkum, Darol (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the implementation of child marriage prevention policies in order to create a Child Friendly Regency in Bangka Regency (Study of Regional Regulation Number 8 of 2022 concerning the Implementation of a Child Friendly Regency) and find out the factors that influence it. The method of analysis in this research is descriptive qualitative method. The data used in this study are primary data from observations and interviews with informants who come from the object of child marriage perpetrators and parents as well as stakeholders from the Bangka Regency Government and secondary data for the period 2021-2023. The results showed that: (1) the implementation of the Child Marriage Prevention policy in order to realize a Child Friendly Regency in Bangka Regency (Study of Regional Regulation Number 8 of 2022 concerning the Implementation of a Child Friendly Regency) has been running well in accordance with the achievement of a decrease in the number of child marriages in Bangka Regency. (2) The factors that influence the implementation of the policy are standard factors and policy objectives, resources, characteristics of implementing agents, attitudes / tendencies of implementers, inter-organizational communication and implementing activities, economic, social and political environment.